خطر تداول النقود الورقية ودور استعمال النقود الحديثة في ظل انتشار وباء كورونا-نماذج عالمية رائدة- (مجلة الواحات للبحوث والدراسات, 2022)
ملخص:تهدف هذه الدراسة لمعالجة موضوع الآثار الاقتصادية للنقود الورقية وتأثير بقائها محل التداول بين الأشخاص خصوصا مع خطر لمس هذه الأوراق إثر زيادة تفشي وباء فيروس كوفيد-19 نهاية سنة 2019 إلى يومنا هذا، ومدى انعكاسه على الاقتصاد العالمي. أظهرت الدراسة أنه في حالة بقاء وزيادة انتشار جائحة كورونا، من الممكن التوجه لتطبيق وسائل الدفع الإلكترونية والشروع في وضع قوانين تضبط التعامل بالنقود الافتراضية لإثبات شرعيتها وقبولها وسط المجتمع كالتحكم فيها من قبل سلطة أو هيئة تتمتع بالمركزية إضافة لاتخاذ إجراءات احترازية لتجنب مخاطرها وتقليص التعامل بالأوراق النقدية لمنع زيادة انتشار الوباء، فالنقود الإلكترونية تعتبر ملاذا آمنا وبديل أنجع للنقود الورقية للحفاظ على الاقتصاد العالمي من الانهيار من جهة وأرواح الملايين من البشر من جهة أخرى في مثل هذه الظروف، في حين تبقى النقود الافتراضية قيد الاختبارات حتى تكتسب شرعية دولية تضبط قوانينها.كلمات دالة: النقود الورقية، النقود الإلكترونية، النقود الافتراضية، أزمة جائحة كورونا.  Abstract:This study deals with the economic effects of paper money and the impact of its remaining in circulation between people, especially with the risk of touching these papers following the increase in the outbreak of the Covid-19 virus at the end of the year 2019 to the present day, and the extent of its impact on the international economy. The study indicated that it is expected that if the survival and increase of the spread of the Corona pandemic, it is possible to go to apply electronic payment methods and start the development of laws controlling the handling of virtual money to prove its legitimacy and acceptance among the community, such as control by a central authority or body in addition to taking precautionary measures to avoid its risks and reduce the handling of banknotes to prevent the increase in the spread of the epidemic, Electronic money is a safe haven and a more effective alternative to paper money to keep the world economy from collapsing on the one hand and the lives of millions of people on the other in such circumstances, while virtual money remains tested until it acquires international legitimacy that regulates its laws.Key words: Paper money, Electronic money, virtual money, corona pandemic crisis.